Docking and molecular dynamics simulations of the ternary complex nisin2:lipid II - Mulholland, Sam; Turpin, Eleanor R.; Bonev, Boyan B.; Hirst, J.D. (Nature Publishing Group, 2016)
Lanthionine antibiotics are an important class of naturally-occurring antimicrobial peptides. The best-known, nisin, is a commercial food preservative. However, structural and mechanistic details on nisin/lipid II membrane complexes are currently lacking. Recently, we have developed empirical force-field parameters to model lantibiotics. Docking and molecular dynamics (MD) simulations have been used to study the nisin2:lipid II complex in bacterial membranes, which has been put forward as the building block of nisin/lipid II binary membrane pores. A Ile1Trp mutation of the N-terminus of nisin has been modelled and docked onto lipid II models; the computed binding affinity increased compared to wildtype. Wild-type nisin was also docked onto three different lipid II structures and a stable 2:1 nisin:lipid II complex formed. This complex was inserted into a membrane. Six independent MD simulations revealed key interactions in the complex, specifically the N terminal engagement of nisin with lipid II at the pyrophosphate and C-terminus of the pentapeptide chain. Nisin2 inserts into the membrane and we propose this is the first step in pore formation, mediated by the nisin N-terminus–lipid II pentapeptide hydrogen bond. The lipid II undecaprenyl chain adopted different conformations in the presence of nisin, which may also have implications for pore formation.